Increased expression of long-isoform thymic stromal lymphopoietin is associated with rheumatoid arthritis and fosters inflammatory responses - Li, Wanlin; Liao, Chenghui; Du, Jing; Hu, Jing; Wang, Lu; Song, Xun; He, Zhendan; Xiao, Xiaohua; Ye, Liang (Frontiers in Immunology, 2023)
Thymic stromal lymphopoietin (TSLP) is a pleiotropic cytokine that is involved in the pathogenesis of inflammatory diseases and asthma, but the expression and biological implications of the existence of two isoforms, long TSLP (lTSLP) and short TSLP (sTSLP), in RA have yet to be elucidated. Here we report that lTSLP is the predominant TSLP isoform in RA and active RA, whereas sTSLP is the major TSLP isoform in inactive RA and healthy controls. lTSLP expression is associated with disease activity, including 28-joint Disease Activity Score (DAS28) and erythrocyte sedimentation rate (ESR), as well as proinflammatory cytokine expression, irrespective of other laboratory parameters. Importantly, lTSLP alone or combined with LPS promotes the expression of proinflammatory cytokines IL-1β, IL-6, and IL-8 in PBMCs of RA, but restrains anti-inflammatory cytokine IL-10 expression in PBMCs of RA. Furthermore, we found that STAT5 signaling is involved in lTSLP-induced inflammatory accumulation in PBMCs of RA. Therefore, these results highlight the clinical significance of lTSLP in RA pathology and inflammatory response in acute-phase disease, which may provide a therapeutic target for RA.